P. falciparum pro-histoaspartic protease (proHAP) protein peptides bind specifically to erythrocytes and inhibit the invasion process in vitro (2005)
Plasmodium falciparum histoaspartic protease (HAP) is an active enzyme involved in haemoglobin degradation. HAP is expressed as an inactive 51-kDa zymogen and is cleaved into an active 37-kDa enzyme. It has been proposed that this kind of protease might be implicated in the parasite's invasion of erythrocytes; however, this protein's role during invasion has still to be determined. Synthetic peptides derived from the HAP precursor (proHAP) were tested in erythrocyte binding assays to identify their possible function in the invasion process. Two proHAP high-activity binding peptides (HABPs) specifically bound to erythrocytes; these peptides were numbered 30609 (101LKNYIKESVKLFNKGLTKKS120) and 30610 (121YLGSEFDNVELKDLANVLSF140). The binding of these two peptides was saturable, presenting nanomolar affinity constants. These peptides interacted with 26- and 45-kDa proteins on the erythrocyte surface; the nature of these receptor sites was studied in peptide binding assays using enzyme-treated erythrocytes. The HABPs showed greater than 90% merozoite invasion inhibition in in vitro assays. Goat serum containing proHAP polymeric peptide antibodies inhibited parasite invasion in vitro.